Analisis Erosi Pada SubDAS Lematang Hulu - Usna Fahliza; Dinar Dwi Anugerah P; Sarino . (Jurusan Teknik Sipil Fakultas Teknik Universitas Sriwijaya, 2013)
At upland areas erosion often occurwhich is caused by soil erosion due to rainfall kinetic energy and other influences such asÂ sensitivity of soil erosion , land use , length and slope of river. The purpose of this study is to calculate the erosivity index and determine the amount of erosion in the sub watershed Lematang Hulu , which is a hilly area in South Sumatra. In this study, the model RUSLE ( Revised Universal Soil Loss Equation ) was used to estimate the amount of erosionÂ caused by kinetic energy that work on the area. The results show the maximum erosion is 5904.146 Tons/Ha/Year,the minimum erosion is 4.168 Tons/Ha/Year, while the average erosion is 2904.157 Tons/Ha/Year. In general, the average erosion rate in the study area is 4,168 Tons/ Ha/Year. Keywords: erosion, RUSLE, erosivity index